Analysis Of Macroeconomic Factors On Indonesian Stock Market Performance Through Stock Trading Volume In The Period 2015-2024 - Wahyu Aji Santoso; Nicko Albart (UNIVED Press, 2026)
Over the past decade, global economic conditions have grown increasingly volatile, with various international challenges affecting national economies. Geopolitical tensions, in particular, have contributed to surging global energy and food prices, potentially driving up inflation and hindering economic growth. Additionally, climate change presents further obstacles to national economic development. In this context, the Composite Stock Price Index (IHSG) is often utilized as an indicator of economic performance, reflecting the health of the stock market, which is closely tied to macroeconomic factors. This study seeks to examine the impact of selected macroeconomic variables namely Gross Domestic Product (GDP), the Dow Jones Index, inflation, exchange rate, and the BI Rate on the IHSG, with stock trading volume considered as a mediating variable. Employing a quantitative research method, the study utilizes panel data regression analysis to test the proposed hypotheses. The sample was selected based on predetermined sampling criteria. The findings reveal that GDP, exchange rate, and the Dow Jones Index significantly affect the IHSG, whereas inflation and the BI Rate do not. Regarding the mediating role of stock trading volume, the results indicate that the exchange rate, BI Rate, and stock trading volume itself do not significantly influence the IHSG. However, inflation is found to have a significant indirect effect on the IHSG through stock trading volume.